Psychological interventions in early psychosis : a treatment handbook - Gleeson, John; McGorry, Patrick D. (J. Wiley, 2004)
Drawing on the expertise of international experts, this practical treatment manual guides mental health professionals in helping first-episode psychotic clients. Chapters are organized according to phase of illness, starting with the pre-psychotic "at risk" phase and extending to protracted recovery from psychotic symptoms